Early Land Plants Today: Index of Liverworts & Hornworts 2015–2016 - Söderström, Lars; Hagborg, Anders; Von Konrat, Matt (Phytotaxa, 2018)
A widely accessible list of known plant species is a fundamental requirement for plant conservation and has vast uses. An index of published names of liverworts and hornworts between 2015 and 2016 is provided as part of a continued effort in working toward maintaining an updated world checklist of these groups. The list herein includes 64 higher taxon names, 225 specific names, 35 infraspecific names, two infrageneric autonyms and 21 infraspecific autonyms for 2015 and 2016, including also names of fossils and invalid and illegitimate names. Thirty-three older names omitted in the earlier indices are included.